1995
DOI: 10.1007/bf03011043
|View full text |Cite
|
Sign up to set email alerts
|

Augmented sensitivity to benzodiazepine in septic shock rats

Abstract: Augmented sensitivity to benzodiazepine in septic shock rats than in both the control and the shamoperated groups, f3H]-diazepam radioligand binding assays demonstrated that the number of receptors in the septic rats was increased in the forebrain (CLP rats; control rats; cerebellum (CLP rats; control rats; and brain stem (CLP rats; control rats; compared with the control and shamoperated rats (P < 0.05). In conclusion, it was considered that th e increased number of benzodiazepine receptors may be one cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…105 Inflammatory mediators increase the insertion of GABA-A receptors in the neuron membrane, 106 and an increase in GABA-A receptor activity has been observed in septic rats. 107,108 Thus, it could be presumed that increased sensitivity to BZ occurs during systemic inflammation. In fact, GABA-A agonists worsen postoperative pain only in the presence of inflammation.…”
Section: 103mentioning
confidence: 99%
“…105 Inflammatory mediators increase the insertion of GABA-A receptors in the neuron membrane, 106 and an increase in GABA-A receptor activity has been observed in septic rats. 107,108 Thus, it could be presumed that increased sensitivity to BZ occurs during systemic inflammation. In fact, GABA-A agonists worsen postoperative pain only in the presence of inflammation.…”
Section: 103mentioning
confidence: 99%
“…Other neurotransmitters may also play a role in the activity of the SNS. Studies have shown that the GABAergic tone in the forebrain of septic animals is enhanced (86)(87)(88), while others indicated that PVN activity can be inhibited by GABA A ergic neuronal inputs from the suprachiasmatic nuclei -an effect that can be reversed by the application of GABA-antagonists (84). Both systems (i.e., the excitatory glutamatergic and inhibitory GABAergic) have been extensively investigated and are known to regulate learning and memory in other regions of the brain, but their regulation of the sympathetic nerve activity remains elusive.…”
Section: Other Targets Of Sympathetic Modulation: Nmethyl-d-aspartatementioning
confidence: 99%
“…T he central nervous system is one of the first organs to be affected by sepsis, but the mechanism by which this dysfunction occurs in this condition has not been defined (1)(2)(3)(4)(5)(6)(7)(8). Several proposed mechanisms for the central nervous system dysfunction induced by sepsis include an alteration in the blood-brain barrier, amino acid disruption, and brain ischemia resulting from a global or regional reduction in the cerebral blood flow (6 -8).…”
mentioning
confidence: 98%